Pengenalan Bahasa Inggris Melalui Literasi Digital untuk Anak Usia Dini: Introduction to English Through Digital Literacy for Early Childhood - Pindha Kaptiningrum; Vira Adoria Sasha (ITScience (Information Technology and Science), 2025)
English vocabulary is often found by Early Childhood. English vocabulary is commonly found on toys, electronic devices and food packaging. English vocabulary introduction to Early Childhood gives understanding of the vocabulary meaning. English vocabulary introduction used Digital Literacy. In the digital era, Digital Literacy is very important to be introduced to Early Childhood. One of the benefits obtained from Digital Literacy is increasing the effectiveness of the learning process and adaptation to the digital age. Digital Literacy introduced to Early Childhood is the use of gadgets or tablets containing vocabularies. The Digital Literacy research was conducted using qualitative descriptive research through interviews, observations, document data and digital materials in the form of videos and voice recordings. The results of the study for the introduction of English are that children can repeat English vocabulary through Digital Literacy, children can communicate orally using Digital Literacy, children can mention the same vocabulary through Digital Literacy, children can compose the same words through Digital Literacy, children enrich English vocabulary through Digital Literacy, children understand several commands through Digital Literacy, children can mention letter symbols through Digital Literacy.